2018
DOI: 10.1016/j.cophys.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the circadian clock in renal physiology

Abstract: Accumulating evidence suggests a critical role for the molecular circadian clock in the regulation of renal function. Here, we consider the most recent advances in our understanding of the relationship between the circadian clock and renal physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…It has also been demonstrated that the pineal gland of rats controls the ion-excretory function of the kidneys and the circadian rhythm of diuresis. Additionally, exogenous light stimuli, forming the daily rhythm of the kidneys, are mediated through the pineal gland [ 34 ]. The light–dark cycle is the main synchronizer of circadian rhythms in the excretion of water and electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the pineal gland of rats controls the ion-excretory function of the kidneys and the circadian rhythm of diuresis. Additionally, exogenous light stimuli, forming the daily rhythm of the kidneys, are mediated through the pineal gland [ 34 ]. The light–dark cycle is the main synchronizer of circadian rhythms in the excretion of water and electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have examined the role of circadian clock in renal function. 28,29 Among the canonical clock genes, Bmal1 is the only one whose sole deletion results in complete loss of circadian rhythms. 30 Most recent research has addressed that Bmal1 plays pivotal roles in renal physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian transcription factors influence renal function (11) and BP (12). The DCT expresses the canonical circadian transcription factors period circadian protein homolog 1 (Per1), Per2, aryl hydrocarbon receptor nuclear translocatorlike protein (Arntl or Bmal1), Clock, and cryptochrome 1/2 (Cry1 and Cry2) (54).…”
Section: Introductionmentioning
confidence: 99%